KENDALI JARAK JAUH MOTOR INDUKSI TIGA FASA BERBASIS IOT - Angga Wahyu Aditya; Restu Mukti Utomo; Fachri Husaini; Aldy Nugroho, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Induction motors have disadvantages in terms of speed regulation. Variable Speed Drive (VSD) allows limited induction motor speed settings. The use of industrial automation systems based on Programmable Logic Control (PLC) and Human Machine Interface (HMI) supported by the Internet of Things (IoT) makes it possible to regulate induction motors in large numbers at relatively the same time. The Modbus communication protocol used by current control devices makes communication between operator and user devices easier. This research produces a control system for two induction motors based on the Altivar 12, connected to an HMI and smartphone for remote control. An induction motor is set up by entering frequency value data and monitoring aspects of three-phase voltage and current, speed, and frequency.